Case report: Prenatal diagnosis of fetal non-compaction cardiomyopathy with bradycardia accompanied by de novo CALM2 mutation - Zhang, Wen; Dai, Xiaohui; Liu, Hanmin; Li, Lei; Zhou, Shu; Zhu, Qi; Chen, Jiao (Frontiers in Pediatrics, 2022)
We herein report what appears to be the first case of fetal non-compaction cardiomyopathy in both ventricles accompanied by a mutation in the calmodulin gene (CALM2). A 25-year-old woman was referred to our hospital at 25+1 weeks of gestation for evaluation of fetal defects. Prenatal echocardiography showed biventricular non-compaction cardiomyopathy with sinus bradycardia. After termination of the pregnancy, fetal biventricular non-compaction cardiomyopathy was confirmed by autopsy and histopathologic examination. Additionally, whole-exome sequencing of genomic DNA demonstrated a de novo heterozygous mutation (c.389A > G; p.D130G) in CALM2, whereas the parents were normal. In this case report, we highlight the importance of prenatal ultrasound and genetic testing in fetal non-compaction cardiomyopathy with arrhythmia.